Branding Strategy, Eco-Friendly Packaging, and Product Image in Increasing the Competitiveness of Local MSMEs: A Study in Asinan Village - Tri Imaliya; Dhevi Dadi Kusumaningtyas; Endang Kustami; Wesly Tumbur ML Tobing (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of branding, environmentally friendly packaging, and product image on the competitiveness of MSME products in Asinan Village, Bawen District, Semarang Regency. Effective branding is believed to be able to create emotional connections with consumers, environmentally friendly packaging becomes an added value that is relevant to the sustainability trend of the modern market, and product image plays an important role in shaping consumer perceptions of product quality and excellence. The research approach uses an associative quantitative method with multiple linear regression analysis techniques. A sample of 30 MSME actors was selected by purposive sampling and analyzed using the SPSS version 25 application. The results showed that branding, environmentally friendly packaging, and product image have a positive and significant effect on product competitiveness, both partially and simultaneously. The coefficient of determination (R²) value of 76.5% indicates the dominant contribution of the three variables to increasing MSME competitiveness. This study provides a practical contribution to village MSME empowerment strategies based on emotional, visual, and market perception values.